Corporate Social Disclosure (CSD) of construction companies in Malaysia / Mustaffa Mohamed Zain and Tamoi Janggu - Mohamed Zain, Mustaffa; Janggu, Tamoi (Faculty of Accountancy & Accounting Research Institute (ARI), 2006)
This article examines the social and environmental disclosures of 37 construction companies listed on Malaysian Stock Exchange from 1998 to 2002. The main objective is to investigate the extent to which Malaysian construction companies disclose social and environmental information and to find out whether the amount of disclosure have relationship with the company's characteristics; size, profitability, leverage, and audit firm. The result provides strong evidence that total CSD is positively related to companies' size and profitability. This implies that larger and more profitable corporations disclose more social and environmental information signaling that they are responsible corporate citizens. Trend analysis of data further confirms that construction companies especially company majority owned by 'corporate owner' in Malaysia are aware of their social responsibility but still at low level. However, the result of the current study rejects the assumption that total CSD is related to audit firm. The test also reveals that there exists no strong evidence to support the relationship between total CSD and leverage.